2017
DOI: 10.3390/nu9030266
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Preschool Overweight and Obesity Amidst the Nutrition Transition: Findings from a National Cross-Sectional Study in Lebanon

Abstract: There is increasing evidence linking early life adiposity to disease risk later in life. This study aims at determining the prevalence and correlates of overweight and obesity among preschoolers in Lebanon. A national cross-sectional survey was conducted amongst 2–5 years old children (n = 525). Socio-demographic, lifestyle, dietary, and anthropometric data were obtained. The prevalence of overweight and obesity was estimated at 6.5% and 2.7%, respectively. Based on stepwise logistic regression for the predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 57 publications
1
48
2
Order By: Relevance
“…The observed positive association between maternal education and adherence to the Traditional dietary pattern may seem contradictory to the fact that maternal education was also found to be significantly associated with a higher risk of preschool overweight in this study. In this context, it is important to note that maternal education may be reflective of a higher socioeconomic status (SES) of the household, suggesting an increased risk of preschool overweight with higher SES [27]. In line with this hypothesis, all the other SES indicators (paternal education; presence of paid helper; type of school) adopted in this study were also found to be associated with a higher risk of overweight amongst Lebanese preschoolers [27].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The observed positive association between maternal education and adherence to the Traditional dietary pattern may seem contradictory to the fact that maternal education was also found to be significantly associated with a higher risk of preschool overweight in this study. In this context, it is important to note that maternal education may be reflective of a higher socioeconomic status (SES) of the household, suggesting an increased risk of preschool overweight with higher SES [27]. In line with this hypothesis, all the other SES indicators (paternal education; presence of paid helper; type of school) adopted in this study were also found to be associated with a higher risk of overweight amongst Lebanese preschoolers [27].…”
Section: Discussionsupporting
confidence: 79%
“…Details about the questionnaire development are shown elsewhere [27]. This study was conducted according to the guidelines laid down in the Declaration of Helsinki and the study protocol and procedures were approved by the Institutional Research Board, American University of Beirut (Protocol number NUT.LN.13).…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Food availability data highlight a shift towards an increasingly energy-dense diet and higher intake of fat in the Region, with a parallel decreasing trend in carbohydrate availability. This trend is confirmed by dietary assessment surveys, which also document high intake of fat, and a shift towards a westernized diet (159,162,(165)(166)(167)(168). Nearly half of the countries in the Region had fat supply levels at or above the reported global average of 81.8 g/person/day (169).…”
Section: Discussionmentioning
confidence: 86%
“…The percentage of intestinal microbiota 281 related publications in the field of obesity research has been soaring in recent years. (Nasreddine et al 2017), so this study reveals the necessity of developed countries to support the 293 developing regions in gut microbiota and obesity-related research in order to address this issue 294 on a global scale.…”
mentioning
confidence: 94%